Experimental Research on Dreaming: State of the Art and Neuropsychoanalytic Perspectives - RUBY, Perrine M. (Frontiers in Psychology, 2011)
Dreaming is still a mystery of human cognition though it has been studied at the experimental level since more than one century. Experimental psychology first investigated dream content and frequency. Then, the neuroscientific approach to dreaming arose at the end of the fifties and rapidly proposed a physiological substrate of dreaming : rapid eye movement sleep (REM). Fifty years later, this hypothesis was challenged because it could not explain all the characteristics of dream reports. The neurophysiological correlates of dreaming, as its functions, remain thus unclear and many questions are left unresolved. Do the representations constituting the dream emerge randomly from the brain or do they surface according to certain parameters? Is the organisation of the dream’s representations chaotic or is it determined by rules? Does dreaming have a meaning? Psychoanalysis provides hypotheses to answer these questions. Until now theses hypotheses have been barely considered in cognitive neuroscience, but the recent creation of neuropsychoanalysis brings new hopes of discussion between the two fields. Considering the psychoanalytical perspective in cognitive neuroscience would provide new directions/leads for dream research and would help to achieve a comprehensive understanding of dreaming. Notably, several subjective issues at the core of psychoanalytic approach, such as the concept of personal meaning, the concept of unconscious episodic memory and the subjects’ history are not addressed or considered in cognitive neuroscience. This paper argues that the expertise of psychoanalysis in singularity and personal meaning is needed to succeed in addressing these issues in cognitive neuroscience and to progress in the understanding of dreaming and psyche.